Pelatihan Teknik Relaksasi Benson untuk Mengatasi Gangguan Tidur pada Lansia di Panti Jompo Wisma Cinta Kasih - Gusti Sumarsih; Arif Rohman Mansur; Windy Freska (Warta Pengabdian Andalas, 2021)
Old age is a natural process that cannot be avoided. It runs continuously and continuously—the elderly experience physiological, biological, psychological, and social setbacks and sleeps pattern disturbances. Insomnia prevalence in Indonesia 2016 in the elderly is relatively high, 67%. Management methods that aim to improve the sleep quality of the elderly in general are by using pharmacology. However, excessive use of drugs will impact the health of the elderly. Thus, an effective and safe non-pharmacological therapy is needed to improve the quality of sleep in the elderly, one of which is the Benson Relaxation Technique. This therapy is a relaxation therapy that involves religious therapy, was at this time, the elderly tend to be closer to God. This relaxation technique was chosen to increase the patient's spiritual activity in dealing with discomfort problems, including sleep disturbances. The method chosen for this community service activity was the method of lectures, counselling, demonstrations, training, and discussions with the elderly as patients and their nurses for repetition in the following days. Evaluation of activities was carried out two months later by asking the nurse to record the sleep quality of the elderly. The training was able to increase the knowledge of patients and their caregivers about the Benson Relaxation Technique to treat sleep disorders in the elderly at the Nursing Home of Wisma Cinta Kasih.